Targeting of client proteins to the VCP/p97/Cdc48 unfolding machine - Meyer, Hemmo; van den Boom, Johannes (Frontiers in Molecular Biosciences, 2023)
The AAA+ ATPase p97 (also called VCP or Cdc48) is a major protein unfolding machine with hundreds of clients in diverse cellular pathways that are critical for cell homeostasis, proliferation and signaling. In this review, we summarize recent advances in understanding how diverse client proteins are targeted to the p97 machine to facilitate client degradation or to strip clients from binding partners for regulation. We describe an elaborate system that is governed by at least two types of alternative adapters. The Ufd1-Npl4 adapter along with accessory adapters targets ubiquitylated clients in the majority of pathways and uses ubiquitin as a universal unfolding tag. In contrast, the family of SEP-domain adapters such as p37 can target clients directly to p97 in a ubiquitin-independent manner. Despite the different targeting strategies, both pathways converge by inserting the client into the p97 pore to initiate a peptide threading mechanism through the central channel of p97 that drives client protein unfolding, protein extraction from membranes and protein complex disassembly processes.